Correlation between internet addiction and overweight/obesity in adolescents - Ida Bagus, Anom Dharma Putra; Windiani, I Gusti Ayu Trisna; Pratiwi, I Gusti Ayu Putu Eka (Indonesian Pediatric Society, 2025)
Background Internet addiction is an emerging health issue in modern society and is associated with a sedentary lifestyle, which contributes to excessive weight gain and obesity. Objective To assess for a correlation between internet addiction and overweight/obesity in adolescents. Methods In this study, secondary data were collected from a previous study (April-July 2022) conducted in junior high schools in Denpasar. Internet addiction was determined using the Indonesian version of the Internet Addiction Test (IAT-Ina) questionnaire. We analyzed the association between internet addiction and overweight/obesity. Results A total of 641 children met the inclusion criteria. Among them, 242 (37.8%) were classified as having internet addiction, while 399 (62.2%) were not. One hundred seven (44.2%) children with internet addiction had overweight/obesity, whereas 145 (36.3%) of non-addicted children had the same condition. A significant positive association was found between internet addiction and overweight/obesity (PR 1.38; 95%CI 1.03 to 1.92; P=0.048). Conclusion Internet addiction is significantly associated with overweight and obesity in adolescents.